2016
DOI: 10.1074/jbc.m116.721936
|View full text |Cite
|
Sign up to set email alerts
|

Iron Export through the Transporter Ferroportin 1 Is Modulated by the Iron Chaperone PCBP2

Abstract: Ferroportin 1 (FPN1) is an iron export protein found in mammals. FPN1 is important for the export of iron across the basolateral membrane of absorptive enterocytes and across the plasma membrane of macrophages. The expression of FPN1 is regulated by hepcidin, which binds to FPN1 and then induces its degradation. Previously, we demonstrated that divalent metal transporter 1 (DMT1) interacts with the intracellular iron chaperone protein poly(rC)-binding protein 2 (PCBP2). Subsequently, PCBP2 receives iron from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 58 publications
(97 reference statements)
4
88
0
Order By: Relevance
“…PCBP1 facilitated iron loading onto ferritin (270). More recently, PCBP2 was shown to interact with DMT1 and FPN1 in hepatocytes, thus possibly functioning in a similar manner to copper chaperones (319, 320). The in vivo significance of these observations is not clear, and whether these proteins function similarly in enterocytes has not yet been investigated.…”
Section: Intestinal Iron Transport: Detailed Mechanistic Descriptionmentioning
confidence: 99%
“…PCBP1 facilitated iron loading onto ferritin (270). More recently, PCBP2 was shown to interact with DMT1 and FPN1 in hepatocytes, thus possibly functioning in a similar manner to copper chaperones (319, 320). The in vivo significance of these observations is not clear, and whether these proteins function similarly in enterocytes has not yet been investigated.…”
Section: Intestinal Iron Transport: Detailed Mechanistic Descriptionmentioning
confidence: 99%
“…In fact, after the first report showing the delivery of iron to Ft by PCBP1 and 2 , it has been shown that these chaperones also deliver iron to both dinuclear (deoxyhypusine hydroxylase) and mononuclear (PHD) iron enzymes . Moreover, PCBP2 interacts with DMT1 and FPN , thus forming a pipeline for iron flux through the cell. Therefore, the identified PCBP partners/targets cover iron transporters, iron storing proteins, and proteins representative of the most important categories of iron‐dependent enzymes.…”
Section: Iron Shuttlingmentioning
confidence: 99%
“…PCBP1 and PCBP2 have been shown to function as iron chaperones that deliver cytosolic iron to ferritin for storage (30,31). Studies in HEp-2 cells, a human epithelial cell line, have found that PCBP2 (but not PCBP1) physically interacts with DMT1 and ferroportin (32,33), but whether this occurs in enterocytes or other cell types remains to be determined. Iron directed for storage in ferritin would serve to retain iron in the enterocyte and prevent its absorption into the body.…”
Section: Dietary Iron Absorption By the Enterocytementioning
confidence: 99%